Ruptured sinus of Valsalva aneurysm: don’t judge a book by its cover! - M.M. Yusuf; A.M. Kumar (Българска кардиология, 2023)
Background: Ruptured Sinus of Valsalva aneurysm (RSOV) has poor prognosis and a high mortality rate. Clinical suspicion is critical for prompt diagnosis and management. Case Presentation: A 33-year-old woman with no comorbidities, presented with persistent cough and recurrent lower respiratory tract infection for 2 years. Echocardiogram showed ruptured right sinus of Valsalva into right ventricle with calciﬁ ed ruptured membrane forming wind-sock morphology. When the patient was taken to the operating room, it was discovered that the RSOV had ruptured into the right atrium. She underwent excision of calciﬁ ed wind-sock tissue along with pericardial patch closure of ruptured right sinus. Conclusions: We discuss a case of an RSOV with atypical presentation, as well as a disparity in imaging features and surgical ﬁ ndings.